Michi no Oku/The End of the Land: contemporary art in Japan and the catastrophic condition - Waite, JH (2021)
The nuclear meltdowns at the Fukushima Daiichi Nuclear Power Station that occurred after the Great East Japan Earthquake and tsunami on March 11, 2011, sparked a long-term international crisis that is at once environmental, social and political. In the face of such an ongoing planetary disaster, what is the role that contemporary art, artists, and cultural workers can play in diagnosing and contesting the disaster? This dissertation focuses on the work of artists including Chim↑Pom, Kota Takeuchi, and Bontaro Dokuyama to explore artistic and cultural responses to the disaster as both a short- and long-term catastrophe, and its effects on the environment and residents of the Fukushima coastal area and beyond. It unpacks the unique tools that artists have brought to this large-scale disaster both marked by its long duration due to the half-lives of the radionuclides and the invisibility of radiation to the human senses, which makes it difficult to see danger in the landscape. A close reading of this landscape and the history embedded in it reveals that the meltdowns at the Daiichi Power Station were just one disaster among many in the region. I read this history through a decolonial lens, to understand the roles that colonisation, extractive economies and a loss of collective agency have had in perpetuating a long-lasting precariousness to human and non-human existence in the area. This longer durational framework is what I call the catastrophic condition, a term I devise to explain the underlying causalities of the nuclear disaster. This dissertation shows how artists have directly responded to and resisted the effects of the nuclear disaster and its effects in Fukushima and Tokyo, and in the process posited new relationships between art production, labor, and anti-colonial practice in Japan.